The new religious movements experience in America - Gallagher, Eugene V. (American religious experience (Greenwood Press (Westport, Conn.)), 2004)
Wherever and whenever they appear, new religious movements always produce conflict. Even as they attract members who enthusiastically embrace their innovative teachings, new religions often provoke strongly negative reactions--often because they challenge established notions of proper religious action, belief, and morality. Opponents of new religious movements often brand them as cults and urge their fellow citizens, their own religions, and even the government to take action against what they see as suspicious and potentially dangerous movements; the members often complain that their motives h.